Preparation method and application of porphyrin MOF / artificial humic acid nano-derived carbon

By combining porphyrin-based MOF with artificial humic acid nanocarbon, efficient porphyrin-based MOF/artificial humic acid nanoderive carbon is prepared, which solves the problem of low efficiency in removing organic pollutants in the prior art, and achieves efficient removal of organic pollutants and economical production of organic pollutants in the water environment.

CN119746831APending Publication Date: 2025-04-04NORTHEAST AGRICULTURAL UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510119092.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing metal organic frame materials are inefficient in removing organic pollutants in water environments and cannot be applied on a large scale. At the same time, nanocarbon materials have high cost, poor dispersion, insufficient performance stability, and difficult to produce on a large scale.

Method used

By combining porphyrin MOF with artificial humic acid nanocarbon, the dispersion and performance of MOF are improved by preparing porphyrin MOF/artificial humic acid nanoderive carbon, and the porous structure and rich surface functional groups of artificial humic acid nanocarbon are used to improve the dispersion and performance of MOF.

Benefits of technology

The removal rate of methylene blue by copper-based porphyrin MOF/artificial humic acid nanoderived carbon has reached 99.41%, and the removal rate of cobalt-based porphyrin MOF/artificial humic acid nanoderived carbon has reached 99.15%, while reducing production costs and is suitable for a variety of wastewater treatments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746831A_ABST
    Figure CN119746831A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of porphyrin MOF / artificial humic acid nano-derived carbon, and belongs to the field of treatment of organic pollutants in a water environment. The invention aims to solve the problems that an existing metal organic framework (MOF) material is low in efficiency of removing organic pollutants and cannot be applied in a large scale, and a nano carbon material modified by the metal organic framework material is high in cost, poor in dispersity, insufficient in performance stability, difficult to produce in a large scale and the like. The preparation method comprises the following steps: 1, preparing porphyrin MOF; 2, preparing artificial humic acid; 3, preparing artificial humic acid nano carbon; and 4, preparing the porphyrin MOF / artificial humic acid nano-derived carbon. The porphyrin MOF / artificial humic acid nano-derived carbon prepared by the invention has the characteristics of porous structure, multiple surface active sites, stable structure and the like; due to the unique structure, organic pollutants in wastewater can be efficiently removed; the safe and effective water body remediation agent is prepared by taking the waste biomass as the raw material, and is suitable for sewage treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of treatment of organic pollutants in water environments, and specifically relates to a preparation method and application of porphyrin MOF / artificial humic acid nano-derived carbon. Background Art

[0002] With the rapid development of industrial scales such as textiles, petroleum processing, and rubber synthesis, a large amount of industrial wastewater containing organic pollution is discharged. If it is not treated, it will cause irreparable harm to the water environment and aquatic organisms, seriously affecting human health. Therefore, it is urgent to prepare new functional materials that can efficiently treat organic pollutants in the water environment to solve the problem of water pollution. Metal organic framework materials (MOF) are often used in water environment remediation due to their strong structural adjustability and porosity, but the poor stability and easy aggregation of MOF still limit their application in the adsorption of pollutants in water. Therefore, selecting a suitable substrate and preparing MOF-based composite materials can reasonably solve these problems, thereby achieving the purpose of efficiently removing organic pollutants in the water environment. At present, many types of MOF composite materials are used for the treatment of environmental wastewater. Among them, nanocarbon-based materials have rich pore structures and large specific surface areas, and stable structures, and have been used as supporting carriers of MOF. However, the existing technology still has some disadvantages, such as: most nanocarbon materials are expensive, the preparation process is complicated, the dispersibility is poor, the performance stability is insufficient, and it is difficult to produce on a large scale. Summary of the invention

[0003] The purpose of the present invention is to solve the problems that the existing metal organic framework materials have low efficiency in removing organic pollutants and cannot be applied on a large scale, and the nanocarbon materials modified by the metal organic framework materials have high cost, poor dispersibility, insufficient performance stability, and difficulty in large-scale production, and to provide a preparation method and application of porphyrin MOF / artificial humic acid nano-derived carbon.

[0004] A method for preparing porphyrin MOF / artificial humic acid nano-derived carbon is specifically completed according to the following steps:

[0005] 1. Preparation of porphyrin MOF:

[0006] The metal salt and tetrakis(4-carboxyphenyl)porphyrin are dissolved in N,N-dimethylformamide, and then heated, condensed and refluxed for a period of time, and then the reaction product is washed with deionized water and dried to obtain a porphyrin MOF;

[0007] 2. Preparation of artificial humic acid:

[0008] First, the biomass waste is washed, dried and crushed to obtain biomass waste powder; the biomass waste powder and the catalyst are dispersed in ultrapure water, and then transferred to a hydrothermal reactor, and then the hydrothermal reactor is placed in an oven for hydrothermal reaction, and then cooled to room temperature to obtain a solid-liquid mixture; the solid-liquid mixture is filtered to collect the liquid; the pH value of the liquid is adjusted to 1 with hydrochloric acid, and the solid is precipitated by standing, and then the precipitated solid matter is washed to neutral with deionized water, dried, and ground into powder to obtain artificial humic acid;

[0009] 3. Preparation of artificial humic acid nanocarbon:

[0010] Artificial humic acid, urea, zinc chloride and potassium chloride are mixed evenly, and then placed in a tube furnace, the tube furnace is flushed with nitrogen for a period of time, and then the temperature is raised to the calcination temperature, calcined for a period of time in a nitrogen atmosphere, cooled to room temperature, and the reaction product is washed with hydrochloric acid and deionized water in turn, and finally dried and ground to obtain highly dispersed artificial humic acid nanocarbon;

[0011] 4. Preparation of porphyrin MOF / artificial humic acid nano-derived carbon:

[0012] The porphyrin MOF and artificial humic acid nanocarbon are mixed evenly, and then placed in a tubular furnace, an inert gas is introduced into the tubular furnace, and then the temperature is raised to a calcination temperature, and oxygen-free calcination is performed in the tubular furnace under an inert atmosphere for a period of time, and the mixture is cooled to room temperature to obtain a reaction product; the reaction product is ground to obtain a porphyrin MOF / artificial humic acid nano-derived carbon.

[0013] A porphyrin-based MOF / artificial humic acid nano-derived carbon is used as an adsorbent for removing organic pollutants from water.

[0014] Principle of the present invention:

[0015] The present invention selects artificial humic acid as a raw material to prepare artificial humic acid nanocarbon (MSNC). The artificial humic acid structure contains a variety of active functional groups and has high stability, and a carbon-based material with rich surface functional groups can be obtained. The structure of the artificial humic acid nanocarbon prepared by the present invention is a porous structure with a larger interlayer spacing, specific surface area and porosity, providing sufficient space for the loading of metal organic framework materials.

[0016] Beneficial effects of the present invention:

[0017] 1. In the present invention, nanocarbon prepared by artificial humic acid is used as the supporting material of porphyrin MOF. The raw material of artificial humic acid, biomass waste, is widely available, cheap and easy to obtain;

[0018] 2. The porphyrin MOF / artificial humic acid nano-derived carbon (MSNC-X-TCPP) prepared by the present invention uses artificial humic acid nano-carbon as a carrier of the porphyrin MOF, which has a larger interlayer spacing, is conducive to the high dispersion of MOF on its surface, and improves the performance of the material;

[0019] 3. The porphyrin MOF / artificial humic acid nano-derived carbon (MSNC-X-TCPP) prepared by the present invention has the advantages of porous structure, stable structure, being able to provide a large number of active sites, and being easier to contact and react with organic pollutant molecules in the water environment;

[0020] 4. The porphyrin MOF / artificial humic acid nano-derived carbon (MSNC-X-TCPP) prepared by the present invention combines the advantages of porphyrin MOF and artificial humic acid nano-carbon, and has a high efficiency in removing organic pollutants in the water environment. The removal rate of copper-based porphyrin MOF / artificial humic acid nano-derived carbon (MSNC-Cu-TCPP) for methylene blue (MB) reaches 99.41%, and the removal rate of cobalt-based porphyrin MOF / artificial humic acid nano-derived carbon (MSNC-Co-TCPP) for naphthalene (NAP) reaches 99.15%;

[0021] 5. The porphyrin MOF / artificial humic acid nano-derived carbon (MSNC-X-TCPP) prepared by the present invention has a simple preparation process, a large preparation yield, and high economic benefits. It can be widely used in various wastewater treatments, can avoid metal leaching in the water environment, and effectively avoid the problem of secondary pollution, which is conducive to its wide application in actual production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 X-ray diffraction images of manganese porphyrin / artificial humic acid nano-derived carbon, manganese-based porphyrin MOF, and artificial humic acid nano-carbon prepared in Example 3 of the present invention;

[0023] Figure 2 Fourier infrared spectroscopic images of manganese porphyrin / artificial humic acid nano-derived carbon, manganese-based porphyrin MOF, and artificial humic acid nano-carbon prepared in Example 3 of the present invention;

[0024] Figure 3 This is a scanning electron microscope image of the artificial humic acid nanocarbon prepared in Example 1;

[0025] Figure 4 This is a scanning electron microscope image of the manganese porphyrin / artificial humic acid nano-derived carbon prepared in Example 3 of the present invention;

[0026] Figure 5 The scanning electron microscope image and EDS image of the manganese porphyrin / artificial humic acid nano-derived carbon prepared in Example 3 of the present invention;

[0027] Figure 6 X-ray diffraction images of porphyrin MOF / artificial humic acid nano-derived carbon prepared in Examples 1-5 of the present invention;

[0028] Figure 7 This is an image of the removal rate of methylene blue by the porphyrin MOF / artificial humic acid nano-derived carbon prepared in Examples 1-5 of the present invention;

[0029] Figure 8 This is an image of the removal rate of naphthalene by the porphyrin MOF / artificial humic acid nano-derived carbon prepared in Examples 1-5 of the present invention;

[0030] Fig. 9 This is an image showing the removal effect of porphyrin MOF / artificial humic acid nano-derived carbon prepared in Examples 1-5 of the present invention on methylene blue and naphthalene. DETAILED DESCRIPTION

[0031] Specific implementation method 1: This implementation method is a method for preparing porphyrin MOF / artificial humic acid nano-derived carbon, which is specifically completed according to the following steps:

[0032] 1. Preparation of porphyrin MOF:

[0033] The metal salt and tetrakis(4-carboxyphenyl)porphyrin are dissolved in N,N-dimethylformamide, and then heated, condensed and refluxed for a period of time, and then the reaction product is washed with deionized water and dried to obtain a porphyrin MOF;

[0034] 2. Preparation of artificial humic acid:

[0035] First, the biomass waste is washed, dried and crushed to obtain biomass waste powder; the biomass waste powder and the catalyst are dispersed in ultrapure water, and then transferred to a hydrothermal reactor, and then the hydrothermal reactor is placed in an oven for hydrothermal reaction, and then cooled to room temperature to obtain a solid-liquid mixture; the solid-liquid mixture is filtered to collect the liquid; the pH value of the liquid is adjusted to 1 with hydrochloric acid, and the solid is precipitated by standing, and then the precipitated solid matter is washed to neutral with deionized water, dried, and ground into powder to obtain artificial humic acid;

[0036] 3. Preparation of artificial humic acid nanocarbon:

[0037] Artificial humic acid, urea, zinc chloride and potassium chloride are mixed evenly, and then placed in a tube furnace, the tube furnace is flushed with nitrogen for a period of time, and then the temperature is raised to the calcination temperature, calcined for a period of time in a nitrogen atmosphere, cooled to room temperature, and the reaction product is washed with hydrochloric acid and deionized water in turn, and finally dried and ground to obtain highly dispersed artificial humic acid nanocarbon;

[0038] 4. Preparation of porphyrin MOF / artificial humic acid nano-derived carbon:

[0039] The porphyrin MOF and artificial humic acid nanocarbon are mixed evenly, and then placed in a tubular furnace, an inert gas is introduced into the tubular furnace, and then the temperature is raised to a calcination temperature, and oxygen-free calcination is performed in the tubular furnace under an inert atmosphere for a period of time, and the mixture is cooled to room temperature to obtain a reaction product; the reaction product is ground to obtain a porphyrin MOF / artificial humic acid nano-derived carbon.

[0040] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: the metal salt described in step 1 is ferric chloride hexahydrate, cupric chloride dihydrate, manganese chloride tetrahydrate, nickel chloride hexahydrate or cobalt chloride hexahydrate; the mass ratio of tetrakis (4-carboxyphenyl) porphyrin described in step 1 to the volume ratio of N, N-dimethylformamide is (1.04 g to 1.5 g): (60 mL to 80 mL). The other steps are the same as those in specific embodiment 1.

[0041] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the molar ratio of the metal salt to tetrakis(4-carboxyphenyl)porphyrin in step 1 is (5-6):1; the temperature of the heating condensation reflux in step 1 is 130°C-150°C, and the time is 5h-7h; the temperature of the drying in step 1 is 60°C-80°C, and the drying time is 10h-12h. The other steps are the same as those in specific embodiment 1 or 2.

[0042] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the biomass waste described in step 2 is corn stalks; the catalyst is potassium hydroxide; the mass volume ratio of the biomass waste powder, catalyst and ultrapure water described in step 2 is 8g:2g:100mL; the temperature of the hydrothermal reaction described in step 2 is 200℃~250℃, and the time of the hydrothermal reaction is 24h~30h. The other steps are the same as specific embodiments 1 to 3.

[0043] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the mass ratio of artificial humic acid, urea, zinc chloride and potassium chloride described in step 3 is (4.50g-5.00g):(4.50g-5.00g):(29.91g-32.00g):(15.09g-17.00g). The other steps are the same as those of specific embodiments 1 to 4.

[0044] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: in step 3, nitrogen is used to flush the tube furnace for 1h to 2h; the heating rate in step 3 is 2℃ / min to 3℃ / min; the calcination temperature in step 3 is 400℃ to 450℃, and the calcination time is 4h to 5h. The other steps are the same as those in specific embodiments 1 to 5.

[0045] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the method of washing the reaction product with hydrochloric acid in step 3 is: immersing the reaction product in hydrochloric acid with a concentration of 1.2 mol / L to 2.0 mol / L and stirring and washing for 24h to 30h, repeating the above washing step twice; in step 3, washing the reaction product with deionized water several times to remove residual hydrochloric acid; the drying temperature in step 3 is 60℃ to 80℃, and the drying time is 10h to 12h. The other steps are the same as those in specific embodiments 1 to 6.

[0046] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the mass ratio of the porphyrin MOF and the artificial humic acid nanocarbon described in step four is (2-4):1; the inert gas described in step four is nitrogen or argon; the heating rate described in step four is 5°C / min-6°C / min; the calcination temperature described in step four is 700°C-900°C, and the calcination temperature is 3h-5h. The other steps are the same as specific embodiments one to seven.

[0047] Specific embodiment 9: This embodiment is a porphyrin MOF / artificial humic acid nano-derived carbon used as an adsorbent to remove organic pollutants in water.

[0048] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that a porphyrin MOF / artificial humic acid nano-derived carbon is used as an adsorbent to remove pollutants in water, which is specifically completed in the following steps:

[0049] A porphyrin-based MOF / artificial humic acid nano-derived carbon is added to water containing pollutants and shaken for a period of time to obtain water with the pollutants removed;

[0050] The organic pollutant is methylene blue or naphthalene;

[0051] The dosage of the porphyrin MOF / artificial humic acid nano-derived carbon is 100 mg to 150 mg;

[0052] The oscillation speed is 900 rpm to 1200 rpm, and the oscillation time is 5 min to 15 min. The other steps are the same as those of the first to ninth embodiments.

[0053] The following examples are used to verify the beneficial effects of the present invention:

[0054] Example 1: A method for preparing iron porphyrin / artificial humic acid nano-derived carbon (MSNC-Fe-TCPP), which is specifically completed by the following steps:

[0055] 1. Preparation of porphyrin MOF:

[0056] 1.96 g of ferric chloride hexahydrate (FeCl3·6H2O) and 1.04 g of tetrakis(4-carboxyphenyl)porphyrin (TCPP) were dissolved in 60 mL of N,N-dimethylformamide (DMF), and then heated at 140°C for 5 h under condensation reflux. The reaction product was washed with deionized water for 5 times and dried in a vacuum drying oven at 60°C for 12 h to obtain an iron-based porphyrin MOF (Fe-TCPP).

[0057] 2. Preparation of artificial humic acid:

[0058] First, the biomass waste is washed, dried and crushed to obtain biomass waste powder; the waste straw powder and the catalyst are dispersed in ultrapure water, and then transferred to a hydrothermal reactor, and then the hydrothermal reactor is placed in an oven for hydrothermal reaction, and then cooled to room temperature to obtain a solid-liquid mixture; the solid-liquid mixture is filtered to collect the liquid; the pH value of the liquid is adjusted to 1 with hydrochloric acid, and the solid is precipitated by standing, and then the precipitated solid matter is washed to neutral with deionized water, dried, and ground into powder with an agate mortar to obtain artificial humic acid (A-HA);

[0059] The mass volume ratio of the waste straw powder, catalyst and ultrapure water described in step 2 is 8g:2g:100mL;

[0060] The biomass waste in step 2 is corn stalks; the catalyst is potassium hydroxide;

[0061] The temperature of the hydrothermal reaction in step 2 is 200° C., and the time of the hydrothermal reaction is 24 h;

[0062] 3. Preparation of artificial humic acid nanocarbon:

[0063] 4.50 g of artificial humic acid, 4.50 g of urea, 29.90 g of zinc chloride and 15.09 g of potassium chloride were ground evenly in an agate mortar, then placed in a tubular furnace, flushed with nitrogen for 1 h, and then heated to 400 ° C at a heating rate of 2 ° C / min, calcined at 400 ° C in a nitrogen atmosphere for 4 h, and cooled to room temperature. The reaction product was first immersed in 1.2 mol / L hydrochloric acid and stirred for 24 h, and the above cleaning steps were repeated twice; the reaction product was washed several times with deionized water to remove residual hydrochloric acid, and finally dried at 60 ° C for 12 h and ground to obtain highly dispersed artificial humic acid nanocarbon (MSNC);

[0064] 4. Preparation of porphyrin MOF / artificial humic acid nano-derived carbon:

[0065] 0.40 g of iron-based porphyrin MOF (Fe-TCPP) and 0.20 g of artificial humic acid nanocarbon (MSNC) were mixed evenly, then placed in a tubular furnace, nitrogen was introduced into the tubular furnace, flushed for 30 minutes, and then heated from room temperature to 700°C at a heating rate of 5°C / min, and oxygen-free calcined in a nitrogen atmosphere and a tubular furnace at a temperature of 700°C for 3 hours, and cooled to room temperature to obtain a reaction product; the reaction product was ground to obtain iron porphyrin / artificial humic acid nano-derived carbon (MSNC-Fe-TCPP).

[0066] Example 2: A method for preparing copper porphyrin / artificial humic acid nano-derived carbon (MSNC-Cu-TCPP), which is specifically completed by the following steps:

[0067] 1. Preparation of porphyrin MOF:

[0068] 1.26 g of copper chloride dihydrate (CuCl2·2H2O) and 1.04 g of tetrakis(4-carboxyphenyl)porphyrin (TCPP) were dissolved in 60 mL of N,N-dimethylformamide (DMF), and then heated at 143 °C for 5 h under condensation reflux. The reaction product was then washed 5 times with deionized water and dried in a vacuum drying oven at 60 °C for 12 h to obtain a copper-based porphyrin MOF (Cu-TCPP).

[0069] 2. Preparation of artificial humic acid:

[0070] First, the biomass waste is washed, dried and crushed to obtain biomass waste powder; the waste straw powder and the catalyst are dispersed in ultrapure water, and then transferred to a hydrothermal reactor, and then the hydrothermal reactor is placed in an oven for hydrothermal reaction, and then cooled to room temperature to obtain a solid-liquid mixture; the solid-liquid mixture is filtered to collect the liquid; the pH value of the liquid is adjusted to 1 with hydrochloric acid, and the solid is precipitated by standing, and then the precipitated solid matter is washed to neutral with deionized water, dried, and ground into powder with an agate mortar to obtain artificial humic acid (A-HA);

[0071] The mass volume ratio of the waste straw powder, catalyst and ultrapure water described in step 2 is 8g:2g:100mL;

[0072] The biomass waste in step 2 is corn stalks; the catalyst is potassium hydroxide;

[0073] The temperature of the hydrothermal reaction in step 2 is 200° C., and the time of the hydrothermal reaction is 24 h;

[0074] 3. Preparation of artificial humic acid nanocarbon:

[0075] 4.50 g of artificial humic acid, 4.50 g of urea, 29.90 g of zinc chloride and 15.09 g of potassium chloride were ground evenly in an agate mortar, then placed in a tubular furnace, flushed with nitrogen for 1 h, and then heated to 400 ° C at a heating rate of 2 ° C / min, calcined at 400 ° C in a nitrogen atmosphere for 4 h, and cooled to room temperature. The reaction product was first immersed in 1.2 mol / L hydrochloric acid and stirred for 24 h, and the above cleaning steps were repeated twice; the reaction product was washed several times with deionized water to remove residual hydrochloric acid, and finally dried at 60 ° C for 12 h and ground to obtain highly dispersed artificial humic acid nanocarbon (MSNC);

[0076] 4. Preparation of porphyrin MOF / artificial humic acid nano-derived carbon:

[0077] 0.40 g of copper-based porphyrin MOF (Cu-TCPP) and 0.20 g of artificial humic acid nanocarbon (MSNC) were mixed evenly, then placed in a tubular furnace, nitrogen was introduced into the tubular furnace, flushed for 30 minutes, and then heated from room temperature to 700°C at a heating rate of 5°C / min, and oxygen-free calcined in a nitrogen atmosphere and a tubular furnace at a temperature of 700°C for 3 hours, and cooled to room temperature to obtain a reaction product; the reaction product was ground to obtain copper porphyrin / artificial humic acid nano-derived carbon (MSNC-Cu-TCPP).

[0078] Example 3: A method for preparing manganese porphyrin / artificial humic acid nano-derived carbon (MSNC-Mn-TCPP), which is specifically completed by the following steps:

[0079] 1. Preparation of porphyrin MOF:

[0080] 1.54 g of manganese chloride tetrahydrate (MnCl2·4H2O) and 1.04 g of tetrakis(4-carboxyphenyl)porphyrin (TCPP) were dissolved in 60 mL of N,N-dimethylformamide (DMF), and then heated at 146 °C for 5 h under condensation reflux. The reaction product was washed with deionized water for 5 times and dried in a vacuum drying oven at 60 °C for 12 h to obtain manganese-based porphyrin MOF (Mn-TCPP).

[0081] 2. Preparation of artificial humic acid:

[0082] First, the biomass waste is washed, dried and crushed to obtain biomass waste powder; the biomass waste powder and the catalyst are dispersed in ultrapure water, and then transferred to a hydrothermal reactor, and then the hydrothermal reactor is placed in an oven for hydrothermal reaction, and then cooled to room temperature to obtain a solid-liquid mixture; the solid-liquid mixture is filtered to collect the liquid; the pH value of the liquid is adjusted to 1 with hydrochloric acid, and the solid is precipitated by standing, and then the precipitated solid matter is washed to neutral with deionized water, dried, and ground into powder with an agate mortar to obtain artificial humic acid (A-HA);

[0083] The mass volume ratio of the waste straw powder, catalyst and ultrapure water described in step 2 is 8g:2g:100mL;

[0084] The biomass waste in step 2 is corn stalks; the catalyst is potassium hydroxide;

[0085] The temperature of the hydrothermal reaction in step 2 is 200° C., and the time of the hydrothermal reaction is 24 h;

[0086] 3. Preparation of artificial humic acid nanocarbon:

[0087] 4.50 g of artificial humic acid, 4.50 g of urea, 29.90 g of zinc chloride and 15.09 g of potassium chloride were ground evenly in an agate mortar, then placed in a tubular furnace, flushed with nitrogen for 1 h, and then heated to 400 ° C at a heating rate of 2 ° C / min, calcined at 400 ° C in a nitrogen atmosphere for 4 h, and cooled to room temperature. The reaction product was first immersed in 1.2 mol / L hydrochloric acid and stirred for 24 h, and the above cleaning steps were repeated twice; the reaction product was washed several times with deionized water to remove residual hydrochloric acid, and finally dried at 60 ° C for 12 h and ground to obtain highly dispersed artificial humic acid nanocarbon (MSNC);

[0088] 4. Preparation of porphyrin MOF / artificial humic acid nano-derived carbon:

[0089] 0.27 g of manganese-based porphyrin MOF (Mn-TCPP) and 0.13 g of artificial humic acid nanocarbon (MSNC) were mixed evenly, then placed in a tubular furnace, nitrogen was introduced into the tubular furnace, flushed for 30 minutes, and then heated from room temperature to 700°C at a heating rate of 5°C / min, and oxygen-free calcined in a tubular furnace at a nitrogen atmosphere and a temperature of 700°C for 3 hours, and cooled to room temperature to obtain a reaction product; the reaction product was ground to obtain manganese porphyrin / artificial humic acid nano-derived carbon (MSNC-Mn-TCPP).

[0090] Example 4: The preparation method of nickel porphyrin / artificial humic acid nano-derived carbon (MSNC-Ni-TCPP) is specifically completed according to the following steps:

[0091] 1. Preparation of porphyrin MOF:

[0092] 1.85 g of nickel chloride hexahydrate (NiCl2·6H2O) and 1.04 g of tetrakis(4-carboxyphenyl)porphyrin (TCPP) were dissolved in 60 mL of N,N-dimethylformamide (DMF), and then heated at 140°C for 5 h under condensation reflux. The reaction product was then washed 5 times with deionized water and dried in a vacuum drying oven at 60°C for 12 h to obtain nickel-based porphyrin MOF (Ni-TCPP).

[0093] 2. Preparation of artificial humic acid:

[0094] First, the biomass waste is washed, dried and crushed to obtain biomass waste powder; the waste straw powder and the catalyst are dispersed in ultrapure water, and then transferred to a hydrothermal reactor, and then the hydrothermal reactor is placed in an oven for hydrothermal reaction, and then cooled to room temperature to obtain a solid-liquid mixture; the solid-liquid mixture is filtered to collect the liquid; the pH value of the liquid is adjusted to 1 with hydrochloric acid, and the solid is precipitated by standing, and then the precipitated solid matter is washed to neutral with deionized water, dried, and ground into powder with an agate mortar to obtain artificial humic acid (A-HA);

[0095] The mass volume ratio of the waste straw powder, catalyst and ultrapure water described in step 2 is 8g:2g:100mL;

[0096] The biomass waste in step 2 is corn stalks; the catalyst is potassium hydroxide;

[0097] The temperature of the hydrothermal reaction in step 2 is 200° C., and the time of the hydrothermal reaction is 24 h;

[0098] 3. Preparation of artificial humic acid nanocarbon:

[0099] 4.50 g of artificial humic acid, 4.50 g of urea, 29.90 g of zinc chloride and 15.09 g of potassium chloride were ground evenly in an agate mortar, then placed in a tubular furnace, flushed with nitrogen for 1 h, and then heated to 400 ° C at a heating rate of 2 ° C / min, calcined at 400 ° C in a nitrogen atmosphere for 4 h, and cooled to room temperature. The reaction product was first immersed in 1.2 mol / L hydrochloric acid and stirred for 24 h, and the above cleaning steps were repeated twice; the reaction product was washed several times with deionized water to remove residual hydrochloric acid, and finally dried at 60 ° C for 12 h and ground to obtain highly dispersed artificial humic acid nanocarbon (MSNC);

[0100] 4. Preparation of porphyrin MOF / artificial humic acid nano-derived carbon:

[0101] 0.28 g of nickel-based porphyrin MOF (Ni-TCPP) and 0.14 g of artificial humic acid nanocarbon (MSNC) were mixed uniformly, and then placed in a tube furnace, nitrogen was introduced into the tube furnace, flushed for 30 min, and then heated from room temperature to 700° C. at a heating rate of 5° C. / min, and oxygen-free calcined in a tube furnace at 700° C. in a nitrogen atmosphere for 3 h, and cooled to room temperature to obtain a reaction product; the reaction product was ground to obtain nickel porphyrin / artificial humic acid nano-derived carbon (MSNC-Ni-TCPP);

[0102] Example 5: The preparation method of cobalt porphyrin / artificial humic acid nano-derived carbon (MSNC-Co-TCPP) is specifically completed by the following steps:

[0103] 1. Preparation of porphyrin MOF:

[0104] 1.86 g of cobalt chloride hexahydrate (CoCl2·6H2O) and 1.04 g of tetrakis(4-carboxyphenyl)porphyrin (TCPP) were dissolved in 60 mL of N,N-dimethylformamide (DMF), and then heated at 135°C for 5 h under condensation reflux. The reaction product was washed 5 times with deionized water and dried in a vacuum drying oven at 60°C for 12 h to obtain a cobalt-based porphyrin MOF (Co-TCPP).

[0105] 2. Preparation of artificial humic acid:

[0106] First, the biomass waste is washed, dried and crushed to obtain biomass waste powder; the waste straw powder and the catalyst are dispersed in ultrapure water, and then transferred to a hydrothermal reactor, and then the hydrothermal reactor is placed in an oven for hydrothermal reaction, and then cooled to room temperature to obtain a solid-liquid mixture; the solid-liquid mixture is filtered to collect the liquid; the pH value of the liquid is adjusted to 1 with hydrochloric acid, and the solid is precipitated by standing, and then the precipitated solid matter is washed to neutral with deionized water, dried, and ground into powder with an agate mortar to obtain artificial humic acid (A-HA);

[0107] The mass volume ratio of the waste straw powder, catalyst and ultrapure water described in step 2 is 8g:2g:100mL;

[0108] The biomass waste in step 2 is corn stalks; the catalyst is potassium hydroxide;

[0109] The temperature of the hydrothermal reaction in step 2 is 200° C., and the time of the hydrothermal reaction is 24 h;

[0110] 3. Preparation of artificial humic acid nanocarbon:

[0111] 4.50 g of artificial humic acid, 4.50 g of urea, 29.90 g of zinc chloride and 15.09 g of potassium chloride were ground evenly in an agate mortar, then placed in a tubular furnace, flushed with nitrogen for 1 h, and then heated to 400 ° C at a heating rate of 2 ° C / min, calcined at 400 ° C in a nitrogen atmosphere for 4 h, and cooled to room temperature. The reaction product was first immersed in 1.2 mol / L hydrochloric acid and stirred for 24 h, and the above cleaning steps were repeated twice; the reaction product was washed several times with deionized water to remove residual hydrochloric acid, and finally dried at 60 ° C for 12 h and ground to obtain highly dispersed artificial humic acid nanocarbon (MSNC);

[0112] 4. Preparation of porphyrin MOF / artificial humic acid nano-derived carbon:

[0113] 0.28 g of cobalt-based porphyrin MOF (Co-TCPP) and 0.14 g of artificial humic acid nanocarbon (MSNC) were mixed evenly, then placed in a tubular furnace, nitrogen was introduced into the tubular furnace, flushed for 30 minutes, and then heated from room temperature to 700°C at a heating rate of 5°C / min, and oxygen-free calcined in a nitrogen atmosphere and a tubular furnace at a temperature of 700°C for 3 hours, and cooled to room temperature to obtain a reaction product; the reaction product was ground to obtain cobalt porphyrin / artificial humic acid nano-derived carbon (MSNC-Co-TCPP).

[0114] Figure 1 X-ray diffraction images of manganese porphyrin / artificial humic acid nano-derived carbon, manganese-based porphyrin MOF, and artificial humic acid nano-carbon prepared in Example 3 of the present invention;

[0115] From the attached Figure 1 From the X-ray diffraction image, it can be seen that the broad peak of MSNC at 2θ=24° is the characteristic peak of amorphous carbon materials. The MSNC-Mn-TCPP prepared by Mn-TCPP and MSNC under oxygen-free calcination has three characteristic peaks at 35°, 41°, and 59°, which are respectively attributed to the (111), (200), and (220) crystal plane diffraction peaks of MnO, indicating that manganese oxides may exist in MSNC-Mn-TCPP.

[0116] Figure 2 Fourier infrared spectroscopic images of manganese porphyrin / artificial humic acid nano-derived carbon, manganese-based porphyrin MOF, and artificial humic acid nano-carbon prepared in Example 3 of the present invention;

[0117] From the attached Figure 2 It can be seen from the Fourier transform infrared spectrum image that MSNC-Mn-TCPP has a stretching vibration peak of Mn-O at 412cm-1, and the stretching vibration peak of Mn-N at 1009cm-1 is weakened.

[0118] Figure 3 This is a scanning electron microscope image of the artificial humic acid nanocarbon prepared in Example 1;

[0119] From the attached Figure 3 From the scanning electron microscope image, it can be seen that artificial humic acid nanocarbon (MSNC) has a porous structure and is composed of many small particles, and the particle size is roughly at the nanometer level.

[0120] Figure 4 This is a scanning electron microscope image of the manganese porphyrin / artificial humic acid nano-derived carbon prepared in Example 3 of the present invention;

[0121] From the attached Figure 4 SEM images at different magnifications show that the surface of manganese porphyrin / artificial humic acid nano-derived carbon presents a complex porous structure and irregular particle structure.

[0122] Figure 5 The scanning electron microscope image and EDS image of the manganese porphyrin / artificial humic acid nano-derived carbon prepared in Example 3 of the present invention;

[0123] From the attached Figure 5 It can be seen from the SEM images and EDS images that carbon, nitrogen, oxygen and manganese elements are evenly distributed on the surface of manganese porphyrin / artificial humic acid nano-derived carbon.

[0124] Figure 6 X-ray diffraction images of porphyrin MOF / artificial humic acid nano-derived carbon prepared in Examples 1-5 of the present invention;

[0125] From the attached Figure 6 It can be seen from the X-ray diffraction images that the porphyrin MOF / artificial humic acid nano-derived carbon both have multiple obvious metal and metal oxide diffraction peaks and have high crystallinity, indicating the successful synthesis of the material.

[0126] Application Example 1:

[0127] 150 mg of the porphyrin MOF / artificial humic acid nano-derived carbon prepared in Examples 1 to 5 was respectively added to 5 conical flasks containing 60 mL of 3 mg / L methylene blue (MB) solution; the mixed solution was then placed in a shaker and shaken at 900 rpm, and the experimental solution was sampled at regular intervals, 4 mL each time, and the samples were filtered through a 0.22 μm water filter membrane, and the concentration of the remaining methylene blue in the solution was determined by an ultraviolet spectrophotometer (λ=664 nm). The experiment was carried out three times in parallel to calculate the standard deviation.

[0128] According to the attached Figure 7 and 9The results show that in the early stage of the experiment, the porphyrin MOF / artificial humic acid nano-derived carbon (MSNC-X-TCPP) exhibited a strong adsorption effect on methylene blue (MB), and the adsorption amount of the composite material remained basically stable after the experiment exceeded 30 minutes. Among them, the copper-based porphyrin MOF / artificial humic acid nano-derived carbon had the highest removal efficiency of MB, reaching 99.41%. It can be seen that the porphyrin MOF / artificial humic acid nano-derived carbon prepared by the present invention has the performance of efficient removal of methylene blue (MB).

[0129] Application Example 2:

[0130] 150 mg of the porphyrin MOF / artificial humic acid nano-derived carbon prepared in Examples 1 to 5 was respectively added to 5 conical flasks containing 60 mL of 3 mg / L naphthalene (NAP) solution; the mixed solution was then placed in a shaker and shaken at 900 rpm. The experimental solution was sampled at regular intervals, 4 mL each time. The samples were filtered through a 0.22 μm water filter membrane and placed in a liquid phase vial. The residual amount of naphthalene (NAP) in the sample was determined by high performance liquid chromatography (λ=255 nm). The experiment was carried out three times in parallel to calculate the standard deviation.

[0131] According to the attached Figure 8 and 9 The results show that in the early stage of the experiment, the porphyrin MOF / artificial humic acid nano-derived carbon (MSNC-X-TCPP) exhibited a strong adsorption effect on naphthalene (NAP), and the adsorption amount of the composite material remained basically stable after the experiment exceeded 15 minutes. Among them, the removal rate of NAP by cobalt porphyrin / artificial humic acid nano-derived carbon was the highest, reaching 99.15%. It can be seen that the porphyrin MOF / artificial humic acid nano-derived carbon prepared by the present invention has the performance of efficient removal of naphthalene (NAP).

Claims

1. A method for preparing porphyrin MOF / artificial humic acid nano-derived carbon, characterized in that The preparation method is specifically completed according to the following steps:

1. Preparation of porphyrin MOF: The metal salt and tetrakis(4-carboxyphenyl)porphyrin are dissolved in N,N-dimethylformamide, and then heated, condensed and refluxed for a period of time, and then the reaction product is washed with deionized water and dried to obtain a porphyrin MOF; 2. Preparation of artificial humic acid: First, the biomass waste is washed, dried and crushed to obtain biomass waste powder; the biomass waste powder and the catalyst are dispersed in ultrapure water, and then transferred to a hydrothermal reactor, and then the hydrothermal reactor is placed in an oven for hydrothermal reaction, and then cooled to room temperature to obtain a solid-liquid mixture; the solid-liquid mixture is filtered to collect the liquid; The pH value of the liquid is adjusted to 1 using hydrochloric acid, and the solid is precipitated by standing. The precipitated solid matter is then washed with deionized water until it is neutral, dried, and ground into powder to obtain artificial humic acid; 3. Preparation of artificial humic acid nanocarbon: Artificial humic acid, urea, zinc chloride and potassium chloride are mixed evenly, and then placed in a tube furnace, the tube furnace is flushed with nitrogen for a period of time, and then the temperature is raised to the calcination temperature, calcined for a period of time in a nitrogen atmosphere, cooled to room temperature, and the reaction product is washed with hydrochloric acid and deionized water in turn, and finally dried and ground to obtain highly dispersed artificial humic acid nanocarbon; 4. Preparation of porphyrin MOF / artificial humic acid nano-derived carbon: The porphyrin MOF and artificial humic acid nanocarbon are mixed evenly, and then placed in a tubular furnace, an inert gas is introduced into the tubular furnace, and then the temperature is raised to a calcination temperature, and oxygen-free calcination is performed in the tubular furnace under an inert atmosphere for a period of time, and the mixture is cooled to room temperature to obtain a reaction product; the reaction product is ground to obtain a porphyrin MOF / artificial humic acid nano-derived carbon.

2. The method for preparing a porphyrin MOF / artificial humic acid nano-derived carbon according to claim 1, characterized in that The metal salt described in step 1 is ferric chloride hexahydrate, cupric chloride dihydrate, manganese chloride tetrahydrate, nickel chloride hexahydrate or cobalt chloride hexahydrate; the mass ratio of tetrakis(4-carboxyphenyl)porphyrin described in step 1 to the volume ratio of N,N-dimethylformamide is (1.04g-1.5g):(60mL-80mL).

3. The method for preparing a porphyrin MOF / artificial humic acid nano-derived carbon according to claim 1, characterized in that The molar ratio of the metal salt to tetrakis(4-carboxyphenyl)porphyrin described in step one is (5-6):1; the temperature of the heating condensation reflux described in step one is 130°C-150°C, and the time is 5h-7h; the temperature of the drying described in step one is 60°C-80°C, and the drying time is 10h-12h.

4. The method for preparing a porphyrin MOF / artificial humic acid nano-derived carbon according to claim 1, characterized in that The biomass waste described in step 2 is corn stalks; the catalyst is potassium hydroxide; the mass volume ratio of the biomass waste powder, catalyst and ultrapure water described in step 2 is 8g:2g:100mL; the temperature of the hydrothermal reaction described in step 2 is 200°C to 250°C, and the time of the hydrothermal reaction is 24h to 30h.

5. The method for preparing a porphyrin MOF / artificial humic acid nano-derived carbon according to claim 1, characterized in that The mass ratio of the artificial humic acid, urea, zinc chloride and potassium chloride described in step three is (4.50g~5.00g):(4.50g~5.00g):(29.91g~32.00g):(15.09g~17.00g).

6. The method for preparing porphyrin MOF / artificial humic acid nano-derived carbon according to claim 1, characterized in that In step three, nitrogen is used to flush the tubular furnace for 1h to 2h; the heating rate described in step three is 2°C / min to 3°C / min; the calcination temperature described in step three is 400°C to 450°C, and the calcination time is 4h to 5h.

7. The method for preparing porphyrin MOF / artificial humic acid nano-derived carbon according to claim 1, characterized in that The method of washing the reaction product with hydrochloric acid in step three is: immersing the reaction product in hydrochloric acid with a concentration of 1.2 mol / L to 2.0 mol / L and stirring and washing for 24 h to 30 h, repeating the above cleaning step twice; in step three, washing the reaction product with deionized water several times to remove residual hydrochloric acid; the drying temperature described in step three is 60°C to 80°C, and the drying time is 10 h to 12 h.

8. The method for preparing porphyrin MOF / artificial humic acid nano-derived carbon according to claim 1, characterized in that The mass ratio of the porphyrin MOF and the artificial humic acid nanocarbon described in step 4 is (2-4):1; the inert gas described in step 4 is nitrogen or argon; the heating rate described in step 4 is 5°C / min-6°C / min; the calcination temperature described in step 4 is 700°C-900°C, and the calcination temperature is 3h-5h.

9. Application of a porphyrin MOF / artificial humic acid nano-derived carbon prepared by the preparation method according to claim 1, characterized in that A porphyrin-based MOF / artificial humic acid nano-derived carbon is used as an adsorbent for removing organic pollutants from water.

10. The use of a porphyrin MOF / artificial humic acid nano-derived carbon according to claim 9, characterized in that A porphyrin-based MOF / artificial humic acid nano-derived carbon is used as an adsorbent to remove pollutants from water, which is specifically accomplished by the following steps: A porphyrin-based MOF / artificial humic acid nano-derived carbon is added to water containing pollutants and shaken for a period of time to obtain water with the pollutants removed; The organic pollutant is methylene blue or naphthalene; The dosage of the porphyrin MOF / artificial humic acid nano-derived carbon is 100 mg to 150 mg; The oscillation speed is 900 rpm to 1200 rpm, and the oscillation time is 5 min to 15 min.

Citation Information

Patent Citations

  • Method for preparing high-specific surface area porous carbon material based on oil tea seed husk and application thereof

    CN105664847A

  • Cu-N-C-based carbon nano sheet and preparation method and application thereof

    CN110124714A

  • Large-size blocky biological framework / MOFs derived composite carbon material and preparation method thereof

    CN113697792A

  • Catalytic oxidation application of spherical nano porous metal-carbon-nitrogen catalyst based on metalloporphyrin polymer

    CN116586089A

  • N and P-rich biomass hierarchical porous carbon derived from water hyacinth as well as preparation method and application of N and P-rich biomass hierarchical porous carbon

    CN117105223A